European species of the Gnaphosa alpica complex (Araneae, Gnaphosidae) - Řezáč, Milan; Růžička, Vlastimil; Oger, Pierre; Řezáčová, Veronika (Zootaxa, 2018)
Members of the genus Gnaphosa belong to the largest gnaphosid spiders. They are particularly interesting in nature conservation as their distribution is mainly restricted to disappearing natural non-forest habitats. In Europe, several Gnaphosa species groups occur. The exclusively Palaearctic group G. bicolor is characterised by a retrolaterally-shifted embolus, which occupies at least part of the middle one-third of the palpal bulb; females have laterally expanded epigyne and often have very elongated median epigynal ducts (Ovtsharenko et al. 1992). So far four species of this group have been identified in Europe, with a fifth species found in Central Asia (G. tarabaevi Ovtsharenko, Platnick & Song, 1992). Two of the European species, G. bicolor (Hahn, 1831) and G. badia (L. Koch, 1866), are well known and their taxonomy and nomenclature is stable, but the same does not hold true for the other two.